2013
DOI: 10.1364/oe.21.000245
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-dependent properties of the cladding modes of a single mode fiber covered with gold nanoparticles

Abstract: The properties of the high order cladding modes of standard optical fibers are measured in real-time during the deposition of gold nanoparticle layers by chemical vapor deposition (CVD). Using a tilted fiber Bragg grating (TFBG), the resonance wavelength and peak-to-peak amplitude of a radially polarized cladding mode resonance located 51 nm away from the core mode reflection resonance shift by 0.17 nm and 13.54 dB respectively during the formation of a ~200 nm thick layer. For the spectrally adjacent azimutha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 22 publications
0
55
0
1
Order By: Relevance
“…51 Single-source, hot-walled CVD experiments were performed using 1 and 2 over a substrate temperature range of 150 -500 ºC using Si [100] substrates on a home-built apparatus. 52 Both precursors produced nanoparticulate films (these included decahedrons, triangles and octahedrons as well as amorphous particles) starting at 300 °C. Pentagonal wires with nanoscale cross-sections were observed sparsely in all depositions, and there was no apparent trend to their growth ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…51 Single-source, hot-walled CVD experiments were performed using 1 and 2 over a substrate temperature range of 150 -500 ºC using Si [100] substrates on a home-built apparatus. 52 Both precursors produced nanoparticulate films (these included decahedrons, triangles and octahedrons as well as amorphous particles) starting at 300 °C. Pentagonal wires with nanoscale cross-sections were observed sparsely in all depositions, and there was no apparent trend to their growth ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were performed on a home-built, low-pressure, hot-walled CVD apparatus. 52 Precursor masses of 50 to 310 mg were delivered from an open-ended vial placed on its side. In the case of 2, a valve was placed between the precursor vial and the furnace which allowed the precursor vial to be loaded in a glovebox and remain air-free during system assembly.…”
Section: 3-diisopropyl-imidazol-2-ylidene Gold(i) Chloride (1-cl)mentioning
confidence: 99%
“…It was reported that absorption and scattering of metal nanoparticles can change transmission spectrum of TFBG by introducing additional losses. 18,19 The Fe 3 O 4 nanoparticles and the magnetic chains/columns formed under magnetic field make the cladding modes of the TFBG lossy through evanescent field. 12 The so-caused loss or attenuation can be described with imaginary part of complex refractive index of the MF.…”
mentioning
confidence: 99%
“…Very recently, gold nanoparticles have been deposited on TFBGs using chemical vapor deposition (CVD) process [34]. Again, a differential behavior was reported between Pand S-polarized lightwaves, the former being the most attenuated in the amplitude spectrum due to an important scattering by the metal nanoparticles.…”
Section: Fig (13)mentioning
confidence: 99%